Online Impulse Buying Behaviour of Indian Small Town Consumers : Scale Development and Validation - Agarwal, Anuradha; Chahar, Bhawna; Bhati, Narender Singh (Indian Journal of Marketing, 2021)
E-commerce companies have started betting big on small towns to look for business opportunities, having a large customer base, and focusing on making customers to buy online as much as possible. Therefore, the study aimed to explore different dimensions of customers’ impulse buying behaviour (IBB) in an online buying environment, and further validating the extracted determinants in small towns of North India. The study included a sample of 304 small town online buyers and used exploratory factor analysis (EFA) to explore the key factors, which resulted into five key determinants of IBB ; Hedonic Online Shopping Motivation, Marketing Stimulus, Impulse Buy, Impulse Buying Tendency, and Situation Stimulus. Further, confirmatory factor analysis (CFA) was performed to evaluate validity and reliability of the identified variables of IBB. The findings revealed good internal consistency among the constructs. Additionally, all measurement model fit indices were found to be under the acceptance range, which indicated no validity concerns in the measurement model. The study provided insights on the complex impulse buying behavior of small town online consumers, which completely differs from the buyers of metro cities. Therefore, the identified determinants of customers’ online IBB will benefit e-tailors by providing them a platform to understand the buying behavior of small town consumers for designing their marketing strategies to serve them better and to gain over the competition in the e-marketplace.